2017
DOI: 10.1089/aid.2016.0159
|View full text |Cite
|
Sign up to set email alerts
|

High HIV-1 Diversity and Prevalence of Transmitted Drug Resistance Among Antiretroviral-Naive HIV-Infected Pregnant Women from Rio de Janeiro, Brazil

Abstract: Antiretroviral (ARV) resistance mutations in human immunodeficiency virus type 1 (HIV-1) infection may reduce the efficacy of prophylactic therapy to prevent mother-to-child transmission (PMTCT) and future treatment options. This study evaluated the diversity and the prevalence of transmitted drug resistance (TDR) in protease (PR) and reverse transcriptase (RT) regions of HIV-1 pol gene among 87 ARV-naive HIV-1-infected pregnant women from Rio de Janeiro, Brazil, between 2012 and 2015. The viral diversity comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…This was consistent with other data from Brazil [12][13][14][15][16][17][18][19][20] with the exception of the southern states, where subtype C has been found to prevail. 21 To a lesser extent, presence of recombinant forms between subtypes B and F, K and between F and subtype F1 was also found.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was consistent with other data from Brazil [12][13][14][15][16][17][18][19][20] with the exception of the southern states, where subtype C has been found to prevail. 21 To a lesser extent, presence of recombinant forms between subtypes B and F, K and between F and subtype F1 was also found.…”
Section: Discussionsupporting
confidence: 92%
“…Subtype C was not observed in the samples, but the prevalence of this subtype is increasing in Brazil, 22 apparently with disease progression characteristics differing from those of subtype B. 23 Subtype F is the second most common form in the cities of Santos 24,25 and Rio de Janeiro 18 and in the states of Minas 12,13,16,17,25,27 Ferreira et al 22 found that the prevalence of transmitted drug resistance in São Paulo and Campinas was 7.6% and that 76.0% of these cases carried mutations for resistance to NNRTIs.…”
Section: Discussionmentioning
confidence: 86%
“…DNA was extracted from 200 μL of each whole blood sample by using the QIAamp DNA Blood Mini kit (Qiagen, Hilden, Germany) according to the manufacturer’s protocol. The partial polymerase ( pol ) gene including protease/reverse transcriptase (PR/RT) region was amplified by nested polymerase chain reaction (PCR) using combinations of primers described elsewhere (Delatorre et al, 2017). The amplified products were analyzed by electrophoresis using agarose gels (1%).…”
Section: Methodsmentioning
confidence: 99%
“…The cDNA synthesis was carried out using 10μL of the RNA in a final reaction volume of 20μL. The mix contained 25mM DNTP mix, 5X M-MLV buffer, 10mM of dithiothreitol (DTT), 40U of RNase OUT ™ (Life Technologies, USA), 0.1mM of MMRTR6 primer (), and 200U of M-MLV enzyme (Life Technologies, USA) [17].…”
Section: Methodsmentioning
confidence: 99%
“…The obtained cDNA was subjected to a nested-PCR, targeting the protease (PR) and reverse transcriptase (RT) fragments of the HIV-1 pol gene, with an expected size of 1302 bp, using the protocol previously described [17]. Successful amplification was checked using a 1% agarose gel.…”
Section: Methodsmentioning
confidence: 99%